Performance during exclusions in female handball - Trejo, A.; Camacho-Cardenosa, M.; Camacho-Cardenosa, A.; Brazo-Syavera, J. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: A temporal exclusion is a predicted sanction in the international handball federation regulation (IHF, 2016). This kind of situations represents a 20% of the total game time (Gutierrez, Fernandez, & Borras, 2010). Teams in superiority may performance at a lower level (Schucker, Hagemann, & Straus, 2013), explaining unexpected results of action during these "advantage" situations (Prieto, Gomez, & Sampaio, 2015). This fact can influence in final result of a game (Prieto, Gomez, & Sampaio, 2015; Trejo & Planas, 2018). Therefore, the aim of this study was to describe the offensive outcomes during exclusions (superiority and inferiority) and compare the final result (winner/loser) conditions in female handball. Methods: Sample consisted in 14 matches from the 2015 PPGG played by those teams that finished the tournament in the four first places. A total of 107 exclusions occurred during those matches. Observational methodology was used. The research team reviewed the videos and collected the data using the software Lince 1.1. Differences between final conditions were analysed using Chi-square test. Results: Figure 1 shows the distribution of the situations related to the type of finalization and in function of the final result of the game (win or lose). Winner teams converted more goals than the loser teams showing a statistically significant difference (p<0.05). Winner teams had a statistically significant lower percentage (p<0.05) of throws out in comparison to loser. Conclusion: Performance during exclusions in female handball is better in key actions (goals and throw out) for winner than for loser teams.